(untitled) (Revista Contexto & Saúde, 2022)
The objective was to analyze the anthropometric profile and the consumption of ultra-processed foods by children of a public school. A descriptive, cross-sectional and quantitative study was conducted with 141 students from a municipal educational institution in Minas Gerais. A structured questionnaire was developed to evaluate demographic and anthropometric variables, as well as food intake. The variable Body Mass Index by Age was used to assess nutritional status; measures such as waist circumference and waist-to-height ratio were used to assess central obesity among students. Food intake was assessed using a food frequency questionnaire, which was adapted to better assess the consumption of ultra-processed foods. Differences between proportions were estimated using Pearson’s χ2 test. In all statistical analyzes, a significance level of 5% was considered. 11.3% (n = 16) of the children were classified as underweight, while 34.0% (n = 48) were overweight. Regarding the presence of central obesity, 7.1% (n = 10) of girls and 9.2% (n = 13) of boys were at increased risk for developing cardiovascular disease. It was found that a significant portion of students with overweight were responsible for the highest consumption of ultra-processed foods. The findings showed a considerable percentage of overweight children and a significant contribution of ultra-processed foods in infant feeding. Thus, it is pertinent to carry out effective food and nutrition education actions aimed at stimulating healthier food consumption and promotion the improvement of nutritional status